2015
DOI: 10.4172/2329-6488.1000214
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF and NGF Modulation by Olive Polyphenols in Alcoholics during Withdrawal

Abstract: Many studies have suggested possible relationships between the neurotrophins brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) and alcohol addiction. Previous reports demonstrated severe changes in these neurotrophins in the serum of alcohol dependent patients and during withdrawal. Alcohol dependence syndromes during consumption and/or withdrawal are also characterized by elevated oxidative stress. Polyphenols, including olive polyphenols, are natural compounds known to possess marked ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…FORD and FORT tests were carried out using two specific kits (both purchased by Callegari, Parma, Italy) following the instruction provided by the manufacturer with minor modification [38,39].…”
Section: Free Oxygen Radicals Defense (Ford) and Free Oxygen Radicalsmentioning
confidence: 99%
“…FORD and FORT tests were carried out using two specific kits (both purchased by Callegari, Parma, Italy) following the instruction provided by the manufacturer with minor modification [38,39].…”
Section: Free Oxygen Radicals Defense (Ford) and Free Oxygen Radicalsmentioning
confidence: 99%
“…Also, the content of antioxidants (polyphenols, resveratrol) in alcoholic beverages (i.e. red wine) may counteract the toxic effect of alcohol per se as shown in FASD/AUD animal models [86][87][88][89][90][91][92][93][94][95][96][97][98]. The effects may vary depending on the dose, duration, exposure period and route of exposure for both the ethanol and the antioxidant.…”
Section: Stressmentioning
confidence: 99%
“…In alcoholic men during withdrawal, it has also been shown that the prolonged consumption of a blend of polyphenols containing hydroxytyrosol, tyrosol and also oleuropein modulated serum levels of neurotrophins, known to play subtle roles in the addiction processes. In particular, the increased level of BDNF, but not NGF, was counteracted by the natural compound supplementation, with a time course, suggesting that monitoring serum BDNF and/or NGF in alcoholics during withdrawal could contribute to characterize alcohol dependence profiles and could be important to improve recovery processes throughout antioxidant compounds supplementation [ 105 ].…”
Section: Gut-brain Axis Deregulationmentioning
confidence: 99%